Using extracellular matrix as the bio-glue for wound repair in the surgery - Zhou, Yingjie; Tang, Li; Mei, Jin; Tao, Shengxiang (Frontiers in Biomaterials Science, 2022)
Bio-glues are gaining ground in medical research to close wounds and fight infections. Among them, the most promising bio-glue is the one prepared from natural materials (fibrin, gelatin, polysaccharides, etc.). Most of these materials are components of the extracellular matrix (ECM) and possess excellent biocompatibility, biodegradability and mechanical strength, which facilitate wound repair. However, there are no studies that utilize the decellularized materials to prepare bio-glues. Outside the wound sealants, approaches that utilize the ECM scaffold to promote tissue repair show tremendous potential. Experimentally, it is unknown if ECM can be successfully transformed to the bio-glue, either alone or in combination with nature biomaterials. In this review, we outline the first attempts at the potential of using ECM to prepare bio-glue for wound repair during the surgery.